Sentiment Analysis of User Reviews of Kitalulus Job Search App on Google Play Store Using Machine Learning - Astrid Ayuzi Putri Hendri Hariadi; Bunga Intan; Armanto (Forum Kerjasama Pendidikan Tinggi (FKPT), 2025)
This study seeks to assess the sentiment of user reviews for the